AKTIVITAS ANTIOKSIDAN DAN KARAKTERISASI SENYAWA BIOAKTIF DENGAN FTIR PADA EKSTRAK ETANOL Sargassum sp. - Elsa Yuliana; Abd. Rohim; Maylina Ilhami Khurniyati; Pinctada Putri Pamungkas; Jihan Novitasari (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Sargassum sp. is a brown seaweed species abundantly found along the coastlines of Indonesia. This study aimed to evaluate antioxidant activity and characterize bioactive compounds from ethanolic extracts of Sargassum sp. using Fourier Transform Infrared Spectroscopy (FTIR). The seaweed samples were collected from Kondang Merak Beach, Malang, Indonesia, and extracted by the maceration method using ethanol as the solvent. Variations in the material-to-solvent ratio (1:10 w/v, 1:20 w/v, and 1:30 w/v) and extraction time (20, 40, and 60 minutes) were applied to determine optimal extraction conditions. Antioxidant activity was assessed using the DPPH method, while total phenolic and total flavonoid contents were measured through colorimetric assays using a spectrophotometer. The results showed that the highest antioxidant activity was achieved at an extraction time of 40 minutes with a solvent ratio of 1:10 (w/v), producing an IC₅₀ value of 5.52 mg/mL, which indicates strong free radical scavenging activity. The highest flavonoid content was obtained at a solvent ratio of 1:30 (w/v), reaching 6.54 mg QE/g. Meanwhile, the highest phenolic content was observed at an extraction time of 60 minutes with the same solvent ratio, amounting to 2.58 mg GAE/g. FTIR analysis revealed major functional groups such as O–H, C=O, and C–O, confirming the presence of phenolic and flavonoid compounds that contribute to antioxidant activity. Overall, these findings demonstrate that ethanolic extracts of Sargassum sp. have strong potential as a natural antioxidant source for functional food applications, supported by chemical characterization through FTIR analysis.